Apelin, a promising target for Alzheimer disease prevention and treatment. (August 2018) - Masoumi, Javad; Abbasloui, Morteza; Parvan, Reza; Mohammadnejad, Daryoush; Pavon-Djavid, Graciela; Barzegari, Abolfazl; Abdolalizadeh, Jalal
Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disease with high outbreak rates. It is estimated that about 35 million individuals around the world suffered from dementia in 2010. AD is expected to increase twofold every 20 years and, by 2030, approximately 65 million people could suffer from this illness. AD is determined clinically by a cognitive impairment and pathologically by the production of amyloid beta (Aβ), neurofibrillary tangles, toxic free radicals and inflammatory mediators in the brain. There is still no treatment to cure or even alter the progressive course of this disease; however, many new therapies are being investigated and are at various stages of clinical trials. Neuropeptides are signaling molecules used by neurons to communicate with each other. One of the important neuropeptides is apelin, which can be isolated from bovine stomach. Apelin and its receptor APJ have been shown to broadly disseminate in the neurons and oligodendrocytes of the central nervous system. Apelin-13 is known to be the predominant neuropeptide in neuroprotection. It is involved in the processes of memory and learning as well as the prevention of neuronal damage. Studies have shown that apelin can directly or indirectly prevent the production of Aβ and reduce its amounts by increasing its degradation. Phosphorylation and accumulation of tau protein may also be inhibited by apelin. Apelin is considered as an anti-inflammatory agent by preventing the production of inflammatory mediators such as interleukin-1β and tumor necrosis factor alpha. It has been shown that in vivo and in vitro anti-apoptotic effects of apelin have prevented the death of neurons. In this review, we describe the various functions of apelin associated with AD and present an integrated overview of recent findings that, in general, recommend apelin as a promising therapeutic agent in the treatment of this ailment. Highlights: We explain the various factors and mechanisms mediated by apelin that may contribute to the prevention and treatment of Alzheimer's disease.